Onion Epithelial Membrane Scaffolds Transfer Corneal Epithelial Layers in Reconstruction Surgery. Issue 14 (16th June 2020) - Wang, Guoliang; Chen, Pei; Wang, Yanzi; Wang, Yixin; Reinach, Peter S.; Xue, Yuhua; Liu, Zuguo; Li, Cheng
Abstract: Plants and their extracts have been used especially in China for more than ten centuries for preventing and treating disease. However, there are only few reports describing their use in animal cell culture and tissue transplantation. In this study, onion epithelial membranes (OEM) is used as scaffolds to support cultures of a variety of cells such as fibroblasts and epithelial cells notably; they maintain the phenotypic characteristics of corneal epithelial cells. This improvement includes preservation of the proliferative potential and stemness of rabbit corneal epithelial cells (RCECs). Such an outcome suggests that this cost‐effective technology warrants further evaluation to determine if OEM is a viable candidate for use as scaffolds in corneal epithelial transplantation surgery. To test this possibility, rabbit corneal epithelial cells expanded on OEM are transplanted to treat corneal epithelial defects in limbal stem cell deficient rabbits. This procedure is successful because it shortens the time required for wound healing to restore losses in corneal epithelial integrity, and forms a more compact and stratified epithelium framework than the untreated group. Ultimately, should they be proven to be effective in other relevant animal model systems, their usefulness for treating wounds in a clinical setting warrants consideration. Abstract : The membrane derived from plant (onion) can be used for the culture of cells, such as corneal epithelial cells and for ocular surface reconstruction. In the subsequent reconstruction of rabbit ocular surface, rabbit corneal epithelial cells expanded on the membrane are successfully transplanted to treat corneal epithelial defects and restore losses in corneal epithelial integrity.